2013
DOI: 10.1371/journal.pone.0070376
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SLITRK1 Variation in Obsessive-Compulsive Disorder

Abstract: Obsessive compulsive disorder (OCD) is a syndrome characterized by recurrent and intrusive thoughts and ritualistic behaviors or mental acts that a person feels compelled to perform. Twin studies, family studies, and segregation analyses provide compelling evidence that OCD has a strong genetic component. The SLITRK1 gene encodes a developmentally regulated stimulator of neurite outgrowth and previous studies have implicated rare variants in this gene in disorders in the OC spectrum, specifically Tourette synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Interest in the SLITRK (Slit- and Trk-like) gene family initially emerged from a chromosomal translocation and follow-up rare variant association study linking SLITRK1 and Tourette's syndrome (Abelson et al, 2005), with support in some but not all subsequent studies (Keen-Kim et al, 2006, Scharf et al, 2008, Miranda et al, 2009, O'Roak et al, 2010, Karagiannidis et al, 2012, Ozomaro et al, 2013). SLITRKs are single-transmembrane proteins containing two extracellular leucine-rich repeat domains, similar to SLIT proteins, and a carboxy-terminal domain similar to tyrosine kinase receptors (Proenca et al, 2011).…”
Section: Genetic Mouse Models Of Ocdmentioning
confidence: 99%
“…Interest in the SLITRK (Slit- and Trk-like) gene family initially emerged from a chromosomal translocation and follow-up rare variant association study linking SLITRK1 and Tourette's syndrome (Abelson et al, 2005), with support in some but not all subsequent studies (Keen-Kim et al, 2006, Scharf et al, 2008, Miranda et al, 2009, O'Roak et al, 2010, Karagiannidis et al, 2012, Ozomaro et al, 2013). SLITRKs are single-transmembrane proteins containing two extracellular leucine-rich repeat domains, similar to SLIT proteins, and a carboxy-terminal domain similar to tyrosine kinase receptors (Proenca et al, 2011).…”
Section: Genetic Mouse Models Of Ocdmentioning
confidence: 99%
“…36 Of note, preliminary sequencing studies of SLITRK1 in patients with OCD and TTM have suggested that rare variation may also be associated with these two related disorders. 73-75 With the advent of genome and exome sequencing, new appreciation of the high frequency of amino-acid altering variations in the general population now supports the need for follow-up studies in larger case-control samples and/or studies of de novo variation in parent-proband trios to determine the significance of these results. 76 …”
Section: Candidate Gene Studies In Ocd and Related Disordersmentioning
confidence: 99%
“…It is notable that variations in the related protein, Slitrk1, have been found in cases of human OCD and TS. 64,75 However, the Slitrk5 knockout mouse seems to be a more useful model for studying OCD and related disorders, as the Slitrk1 knockout mouse has been shown to have increased anxiety behaviors but studies have not detected additional behavioral abnormalities consistent with OCD behaviors such as excessive self-grooming. 88 …”
Section: Model Systems In Ocd and Related Disordersmentioning
confidence: 99%
“…In addition, this gene has been implicated in comorbid disorders, such as OCD and trichotillomania (Abelson et al, 2005; Zuchner et al, 2006; Ozomaro et al, 2013). …”
Section: Animal Models Based On Genetic Manipulationsmentioning
confidence: 99%